THEORETICAL AND PRACTICAL SUPPORT OF INCLUSIVE EDUCATION IN FOREIGN COUNTRIES - Qurbonova Maxtuma Fazliddinovna (Modern American Journals, 2025)
This study examines the theoretical foundations and practical mechanisms of inclusive education as implemented in foreign countries, with a particular focus on pedagogical, institutional, and socio-cultural dimensions. Inclusive education is increasingly recognized worldwide as a fundamental principle of educational equity, aiming to ensure equal access to quality education for all learners regardless of physical, intellectual, social, emotional, linguistic, or cultural differences. The relevance of this research is обусловлена the global shift from segregated and integrative models toward fully inclusive educational systems that emphasize participation, diversity, and learner-centered pedagogy. The study analyzes how inclusive education is conceptually framed in international pedagogical theory and how these theoretical principles are translated into practice across different national contexts. Special attention is given to the role of state policy, legal frameworks, teacher preparation systems, and intersectoral cooperation in supporting inclusive practices. The research draws on comparative pedagogical analysis of inclusive education models in Europe, North America, and selected Asian countries, highlighting both common trends and context-specific approaches. Key aspects considered include curriculum adaptation, differentiated instruction, universal design for learning, collaborative teaching models, and the use of support services within mainstream educational settings. The study also explores how teacher professional development, school leadership, and community involvement contribute to the sustainability of inclusive education. By synthesizing international experience, the research identifies effective strategies and persistent challenges in implementing inclusive education, such as resource constraints, teacher readiness, and attitudinal barriers. The findings emphasize that successful inclusive education requires not only structural reforms but also a shift in pedagogical thinking toward diversity as an educational value rather than a deficit. The study’s outcomes provide a theoretical and practical basis for enhancing inclusive education policies and pedagogical practices in higher pedagogical institutions, contributing to the preparation of future teachers capable of working effectively in diverse learning environments.
Keywords: inclusive education, pedagogical support, international experience, educational equity, teacher preparation, differentiated instruction, inclusive policy, learner diversity.